Impact of an Educational Intervention on the Use of Social Media in the Digital Literacy of Older Adults - Sánchez Guzmán, Óscar Favián; Rozo Caballero, Rosalba; HERRERA ALONSO, EDNA FAISULY (PEM. Revista de Didáctica, Evaluación e Innovación, 2025)
Currently, older adults represent one of the most lagging population groups in the face of rapid technological progress, which limits their active participation in digital environments and their social appropriation of knowledge. In response to this issue, the present study evaluated the impact of an educational intervention aimed at strengthening digital literacy among older adults through the functional use of social networks. A pre-experimental design was applied with a group of 15 participants belonging to a community digital inclusion program. The instrument used was a 10-item questionnaire that assessed knowledge about the Internet, WiFi connectivity, email, and the management of social networks (Facebook, WhatsApp, and YouTube). The intervention was developed through a MOOC on the institutional platform of the University of Cundinamarca with through practical workshops and personalized tutoring, focusing on meaningful learning and technological autonomy. The results showed a substantial improvement in the level of digital literacy: the average of correct answers increased from 44.9% in the pretest to 85.9% in the posttest, with a 41% improvement. The Student’s t-test for related samples indicated significant differences (t(14) = 15.46; p < 0.001), confirming the effectiveness of the implemented educational strategy. In conclusion, the pedagogical use of social networks promotes digital inclusion and the social appropriation of knowledge, strengthening the technological competencies and participation of older adults in the knowledge society.